Pemilihan Pegawai Terbaik Menggunakan Metode Simple Additive Weighting di Asisten Deputi Pengembangan Staf Aparatur Kementerian Pariwisata Jakarta - Priatno, Priatno; Partawijaya, Wahyu Sofyan; Ryansyah, Muhamad (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Deputy Assistant of Human Resources Development Apparatus of the Ministry of Tourism Jakarta is a government agency engaged in the development of personnel of the apparatus. Employees are very important resources to determine the success of a work unit. Efforts to improve the quality of performance of a civil servant is the selection of the best employees. The best employee selection is an award given for work performance, behavior and service. Decision Support System (SPK) that can help make it easier to determine an employee can be said to be worthy of being awarded as the best employee. In this study the decision-making calculation method used is Simple Additive Weighting (SAW) with 6 criteria, namely service orientation, integrity, commitment, discipline, cooperation, leadership. The ranking process is carried out through several stages starting with the grading of criteria, weighting, matching ranking, normalization, and ranking so as to produce the value of each criterion which is stated to have met the best employee selection criteria at the Deputy Assistant of HR Development of the Ministry of Tourism in Jakarta.